The Anti-Inflammatory Effect of Vitamin K in Aging - Anber, Zainab Nazar Hasan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Vitamin K is a fundamental enzymatic co-factor implicated in the carboxylation of several vitamin K dependent proteins involved in the pathogenesis of certain age – related diseases. Inflammation is realized as an important factor in such diseases. Vitamin K is recognized to play an anti-inflammatory behavior that is distinct of its action as an enzymatic co- factor by suppressing many signaling pathways mainly the nuclear factor κB (NF-κB) signal transduction pathway. As well as to play a role as an antioxidant versus the generation of reactive oxidative species (ROS). The purpose of this review is to focus on the protective function of vitamin K as an anti-inflammatory agent in these age- associated diseases. And the importance of vitamin K complement as a protective nutrient in aging.